2020
DOI: 10.1007/s10354-020-00783-w
|View full text |Cite
|
Sign up to set email alerts
|

Hemiagenesis of the thyroid gland detected by coincidence—what is the clinical relevance?

Abstract: Summary Hemiagenesis of the thyroid gland (THA) represents a rare congenital anomaly. It is characterized by the absence of one thyroid lobe, and sometimes the isthmus as well. It can occur with all kinds of other thyroid pathologies that may be present in the remaining thyroid lobe. A case of a 21-year-old male patient is presented; he sought a thyroid consultation because of hair loss, fatigue, and problems concentrating, thus raising the suspicion of hypothyroidism. Thyroid function was normal, but sonograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(110 reference statements)
0
9
0
Order By: Relevance
“…THA is a rare congenital anomaly of the thyroid gland with about 800 cases reported in the literature until 2020 [5]. The true prevalence of THA is not clearly known, with the reported prevalence rates varying between 0.05 to 0.5 % [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THA is a rare congenital anomaly of the thyroid gland with about 800 cases reported in the literature until 2020 [5]. The true prevalence of THA is not clearly known, with the reported prevalence rates varying between 0.05 to 0.5 % [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, the etiology still remains unclear [4]. Genetic aberrations may have a role in the etiology of this disorder, as reported in monozygotic twin studies [5].…”
Section: Introductionmentioning
confidence: 99%
“…Following ultrasound, thyroid scintigraphy using technetium or iodine detects the functional anatomy of the thyroid gland with the added advantage of being able to detect the presence of hyperactivity and increased diffuse uptake in the glands [ 36 ]. Furthermore, scintigraphy can be used to detect ectopic thyroid tissue as well as diagnose thyroid pathologies in the remaining lobe associated with hyperthyroidism or a nodule suspicious of cancer [ 3 ]. The disadvantage of scintigraphy is due to artifacts related to the inability to view a thyroid lobe due to cancer, a contralateral autonomous solitary thyroid nodule suppressing normal tissue function, inflammatory and infiltrative pathologies of the thyroid gland, also the use of computed tomography scans have been helpful in further establishing the diagnosis.…”
Section: Reviewmentioning
confidence: 99%
“…Anomalies in their development can lead to abnormalities in the structure or function of which THA is a part [ 2 ]. Genetic abnormalities may have a role to play in the etiology of THA as reported in monozygotic twins [ 3 ]. Different studies have shown that in 80% of cases, it affects the left lobe with an L:R ratio of 4:1.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a few previous reports described the imaging findings of thyroid hemiagenesis as absence of the one thyroid lobe in scintigraphy, ultrasonography (US), and computed tomography (CT) [ 7 10 ]. However, absence of one thyroid lobe in imaging study may strongly suggest the diagnosis of hemithyroidectomy state in patients for whom no or little clinical information is available.…”
Section: Introductionmentioning
confidence: 99%